Statistics of QR code usage in polygraphy - Bilchuk, O. S.; Bokareva, Y. S. (European Scientific Platform, 2022)
Music plays a special role in the life of every person. Music is a harmonious combination of sounds. The whole world consists of sounds. People want to listen to music in any place. And, of course, people want to know more about their favorite artists. Modern technology makes it possible to combine these aspects in a printed publication. The most relevant type of such publication is magazines. It should also be remembered that the multimedia environment opens up new opportunities for creating and distributing media content.
Keywords: QR code; polygraphy